English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

4 answers

(x^2 + 2x + 1) + (y^2 - 6y + 9) -10 - 6 = 0
(x+1)^2 + (y - 3)^2 = 16
the circle of center (-1,3) and radius 4

2007-01-19 05:19:01 · answer #1 · answered by Anonymous · 0 0

4

(x+1)^2 + (y-3)^2 = 16

2007-01-19 13:01:08 · answer #2 · answered by trichbopper 4 · 0 0

tthe center is the point(-1,3) and the radius is sqrt(1+9+6) =4

2007-01-19 13:03:35 · answer #3 · answered by santmann2002 7 · 0 0

I guess you need to know this:

Standard form for circle:

(x-h)²+(y-k)²=r²

r = radius
center = (h,k)

2007-01-19 13:01:36 · answer #4 · answered by bequalming 5 · 0 0

fedest.com, questions and answers